An analysis on the effectiveness of conciliation and arbitration as labour dispute resolution mechanisms Zimbabwe - Mudoni, Tapiwa Vincent (Midlands State University, 2017)
A bone of contention always arises in labour relations and ADR systems have been established so as to rectify labour disputes. Zimbabwe has a dual juncture labour system whereby the labour laws are not harmonized as both private and public sector are governed by different labour statutes. The Public Service Regulations Act governs the Public service employees excluding the security forces whereas the Labour Act governs private sector employees, metropolitan councils and parastatals. The study addressed how labour disputes are resolved through conciliation and arbitration procedures in Zimbabwe. The underlying principles of conciliation and arbitration practice in the country which involves a number of factors namely accessibility, speed, privacy and costs which provides for parties concerned to seek justice. It can be noted that there are major drawbacks to conciliation and arbitration practice in Zimbabwe due to a number of challenges that are encountered which include the lack of competence amongst conciliators and arbitrators as there are no clear specific guidelines on how conciliation proceedings are conducted with each conciliator conducts proceedings in his or her own way deemed necessary as there are no training services offered by the Ministry of Labour on how disputes should be rectified. The study found out that the ADR conciliation and arbitration practice in Zimbabwe is ineffective as it lacks enforceable mechanisms for its determinations and awards and as a result disputes take a longer period to be finalized as they spill into local courts for registration and enforcement. The regulatory environment on labour relations is shallow in the sense that it lacks clear indications on the resolution of industrial conflicts in the provision of the time frame labour disputes are to be administered and finalized. The conflicting legislation which is often confusing thereby limiting effective operations in the resolution of disputes. The Labour Amendment Act distinguished disputes of rights and of interests whereby disputes of right upon failure of conciliation, the labour officer may issue a ruling or refer the dispute to compulsory arbitration. The legislation has no proper indications on the classifications of the distinguished disputes affecting the resolution of disputes in ADR. Various reforms of the labour legislation needs to be put forward so that ADR can be effective.